The teaching dilemma of health education teachers in China and path exploration: a cross-sectional study of Guangdong Province - Wang, Zhen; Zhu, Lin (Frontiers in Public Health, 2025)
BackgroundSchool-based health education is a major way to improve the health literacy of children and adolescents, the teaching difficulty of health education teachers will directly affect its implementation. This study aimed to understand the degree of teaching difficulty of health education teachers in Guangdong Province and to explore the influencing factors.MethodsA self-made questionnaire was used to survey health education teachers of 232 primary and secondary schools in Guangdong Province. The survey included three components: teachers’ basic information, teaching situation, and school level investigation. Data were analyzed using the chi-square test for single factors and a binary logistic regression model for multiple factors.ResultsA total of 5,416 (97.69% were valid) teachers responded to the questionnaire in the survey, and 44.26% were health education teachers. Health education teachers who were engaged in full-time jobs and had health-related training experience, and health education teachers whose schools provided uniform teaching materials and put a high value on health education, were less difficult to teach. Health education teachers whose schools had teaching standards and evaluation criteria were more difficult to teach. Among these factors, the occupation type and health-related training experience were the main factors affecting teaching difficulty.ConclusionThe teaching difficulty of health education teachers in primary and secondary schools in Guangdong Province is high. Strategies for building full-time health education teacher groups and enhancing health education training for teachers should be adopted to reduce teaching difficulty.